Increasing The Growth and Yield of Lowland Rice (Oryza Sativa L.) with Optimum Dosage and Frequency of Potassium - Arman Effendi; Sri Yoseva; Suningsih Suningsih (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Lowland rice is a commodity crop that is very influential in the survival of many people, especially inhabitants in most Asian countries, especially Indonesia. Rice is the staple food of Indonesian people, the shortage of which can result in complications for the country. In connection with this food security issue, it is necessary to make efforts to prevent food shortages. The national production capacity of rice must be increased. The long-term goal is to increase the productivity of rice plants to support Indonesia towards rice self-sufficiency. This study has a short-term objective, namely, to determine the effect of potassium fertilizer and to obtain the best dose on the growth and production of rice plants. This was a factorial experiment using a completely randomized design (CRD) with two factors: the KCl fertilizer dosage and the frequency of fertilizer application. The results showed that the best treatment was with a potassium fertilizer dosage of 150 kg ha-1 with a frequency of 2-time fertilizer application.